Indonesian pre-service students’ preferences, frequencies, and perceptions of using mobile devices in language learning across departments and genders - MirantyDelsa; WidiatiUtami (Proceder: Applied Linguistics, Literature, and Language Education, 2025)
University students worldwide use mobile devices for language learning, but little is known about how mobile devices relate to Indonesian pre-service students across departments and genders. This study examined Indonesian pre-service students’ preferences, frequencies, and perceptions of how English Education and Mathematic Education departments use mobile devices for language learning across departments and genders. The participants in this study were first-year to seventh-year pre-service students from two departments at a public university in Banten province. The samples were three hundred and two pre-service students who studied English as a foreign language at an Indonesian public university in Banten province, including 246 females (150 from English Education and 96 from Mathematics Education) and 56 males (42 from English and 14 from Mathematics). The study utilized a quantitative research design, employing an online survey with a closed-ended questionnaire as the primary instrument for data collection. The researchers then categorized and interpreted the survey data descriptively and quantitatively to answer the study’s questions. The study found that most female students from both departments use smartphones almost daily, followed by laptops, and they positively perceive using mobile devices in learning languages. Due to cost, spare parts, and data sharing, the students from both departments rarely use other mobile devices such as iPads, tablets, smartwatches, and Google Glass. Next, this study demonstrated the benefits of learning environments, including how pre-service students use mobile devices to learn English as a foreign language, more technical support for using technologies in ELT settings, and the impact on language teaching.